Pre-Calculus 12

posted by .

Solve using logarithm:
2^(4x+1)=3^x

  • Pre-Calculus 12 -

    take logs of both sides

    log 2^(4x+1) = log 3^x
    use rules of logs
    (4x+1)log2 = xlog3
    4xlog2 + log2 = xlog3
    4xlog2 - xlog3 = -log2
    x(4log2 - log3) = -log2
    x = -log2/(4log2 - log3)
    x = log2/(log3 - 4log2)
    = ..

    let the button-pushing begin

  • Pre-Calculus 12 -

    Thank you!

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. pre-calculus

    given that c is the logarithm of x in base a, and d is the logarithm of x in base b, find the general statement that expresses the log of x in base ab, in terms of c and d. [*subscripts not included: a,b,ab] loga_x=c ; logb_x=d ...logab_x …
  2. pre calculus

    Write the expression below as a single logarithm. 2in(x+4)-in((x^(2)+x-12)/(x))
  3. pre calculus

    Write the expression below as a single logarithm. Need to know how to work this! ln(x-5/x^2 - 1) - ln (x^2 - 2x -15/x + 1)
  4. pre-calculus

    write the expression as a simple logarithm. express powers. In(x/x-5)+In(x+5/x)-In(x^2-25)
  5. Pre-Calculus - Reiny

    Reiny you helped me with this logarithm yesterday: How did you write it out as log2 ( √A / B^3 ) Laws of logarithms combine, write as a single logarithm Need help on this question please, Im stuck, don't know where to go abouts …
  6. Pre-Calculus

    How to solve this problem by using logarithm: David inherits $10000 and invests in a Guaranteed Investment Certificate (GIC) that earns 6%, compounded semi-annually. How long will it take for the GIC to be worth $11000.
  7. Logarithm help

    using logarithms to solve exponential equations. 5^1+x = 2^1-x I need exact numbers. I did one on my own already. 5^x-1 = 9 5^x-1 = 9 log(5^x-1) = log9 (log5)(x-1) = log9 x-1 = (log9/log5) x= (log9/log5)-1 x = 2.3652 Logarithm help …
  8. math: pre-calculus

    Write the expression as a single logarithm. Ln(e^3y)+ln(ey)-4
  9. Pre-Calculus

    Solve the system of equations using matrices. Use Gaussian elimination with back-substitution. x + y + z = -5 x - y + 3z = -1 4x + y + z = -2 I really need help.. 1 1 1 -5 1 -1 3 -1 4 1 1 1 -2 I've done so many different methods to …
  10. Pre-Calculus 12

    Write the following expression as a single logarithm: 4 log 3 + 2

More Similar Questions